Development of monitoring and control system for wastewater treatment process - Aung Maw (2008)
The main focus is to incorporate new equipment controls, develop an Human Machine Interface linked to the pilot plant and fully integrate the pilot plant by use of PLC. It shall be able to conclude the optimum control parameters, expected NEWater quality, and cost effectiveness in UF and RO process.